1984
DOI: 10.1113/jphysiol.1984.sp015229
|View full text |Cite
|
Sign up to set email alerts
|

The response to hypoxia of arterial chemoreceptors in fetal sheep and new‐born lambs.

Abstract: SUMMARY1. Carotid chemoreceptor activity was detected in each of fourteen halothane or pentobarbitone anaesthetized exteriorized fetal lambs of 90-143 days gestational age.Activity was about 5 Hz at a Pa°, of 25 mmHg and it increased as Pa°2 was reduced, either by compressing the umbilical cord or by reducing the (Flo2) oxygen fraction of the gas used to ventilate the ewe.2. Activity increased briskly when 1-2 ml CO2-saturated saline was injected retrogradely into the lingual artery, but not when saline of pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
134
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(143 citation statements)
references
References 18 publications
8
134
1
Order By: Relevance
“…In newborn lambs, an increase in ventilation stimulates pulmonary stretch receptors and thus can counteract the chemoreceptor-induced decrease in heart rate (1 5). However, resetting of the aortic and carotid chemoreceptor bodies after birth, as measured by their nerve activities, has been reported in newborn lambs (9,13). The functional changes underlying the difference in response to hypoxemia between the fetus and the newborn remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In newborn lambs, an increase in ventilation stimulates pulmonary stretch receptors and thus can counteract the chemoreceptor-induced decrease in heart rate (1 5). However, resetting of the aortic and carotid chemoreceptor bodies after birth, as measured by their nerve activities, has been reported in newborn lambs (9,13). The functional changes underlying the difference in response to hypoxemia between the fetus and the newborn remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that the carotid chemoreceptors are inactive in the fetal physiologic range (8), although carotid-nerve activity has been recorded in fetal lambs (9). However, all of these experiments were performed in acutely exteriorized fetal lambs, whereas the ewe was given chloralose anesthesia.…”
mentioning
confidence: 99%
“…The mechanism of this late fall is less clear. Among the possible mechanisms are recruitment of other peripheral chemoreceptor input (Bartelds et al, 1993), a synergistic effect of severe hypercarbia on carotid chemoreceptors (Blanco et al, 1984), a direct effect of ischemia on cardiac pacemaker cells (Gryshchenko et al, 2002), and an activation of the cardioinhibitory Bezold-Jarisch reflex (Aviado and Guevara, 2001;Dawes and Comroe, Jr., 1954). This latter reflex originates from the stimulation of both mechanically and chemically sensitive receptors in the ventricle which can be elicited by coronary ischemia and asphyxia (Thoren, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…In the 10-day-old lamb, the magnitude of the rapid response to inspired hypercapnic gas, which is mediated by the peripheral chemoreceptors, is small (9,14,50). Calculations based on the data of Carroll et al (14), and our own unpublished data, suggest that within the brief three-to four-breath time span of the ventilatory period of PB in the lamb, only an 8% increase in ventilation is predicted when a CO 2 stimulus similar to that expected during PB is applied (ϳ7 Torr; Ref.…”
Section: Theoretical Modelmentioning
confidence: 99%